ETHNIC PROCESSES IN TURKESTAN IN THE SECOND HALF OF THE XIX CENTURY (Scientific journal of the Fergana State University, 2024)
The article describes ethnic processes in the Turkestan region on the basis of historical sources and literature. In particular, in the Zarafshan Valley, Kashkadarya and Surkhandarya oases, in the Vakhsh, Kofirnikhon, Pyanj and Murghab river oases on the territory of modern Tajikistan, in Margilan, Uzgen, Andijan, Namangan, Tashkent, Shymkent, Turkestan, Avliet, Pishak. , Suzak, Suzak, Suzak information on the ethnic composition of the population living in cities and towns such as Khiva, Urgench, Kat, Stary Urgench, Khazarasp, Kungrad, Khojaili, Kurdar (now Chimbay). It also covers issues such as ethnic processes and resettlement policies that the Russian Empire underwent after the occupation of Turkestan.